THE ANALYSIS OF ILLOCUTIONARY ACTS IN COMIC “THE ADVENTURES OF TINTIN VOLUME 8“ - Septiana Sibuea, Sryetti (Jurnal Ilmu Budaya, 2021)
This research discusses the types, functions, and dominant types contained in the conversation of the main character in the comic " The Adventures of Tintin Volume 8 “. Comic is one of the picture books which are popular with youth and children. This comic tells the characters of Tintin, who like the main character, plays a detective. A picture that represents the character’s actions reinforces each utterance presented by the characters. The focus of the study in this discussion is to answer the research statement, namely the types of Illocutionary Acts in the Comic “ The Adventures of Tintin Vol 8 “ and the functions as well as the dominant types found in the conversation. In this research, the writer found out the types of Illocutionary acts from the 3 stories are Representative, Directive, Expressive and Commissive. From the 3 stories, there are slightly different functions depending on the situation of each story. The dominant types are representatives. Its shows that Tintin representing the statement from his acts to make the listener believe in his word.